Cerebrospinal Fluid Biomarkers of Alzheimer Disease - Kseniya V. Nevzorova; Yuliya A. Shpilyukova; Аlla A. Shabalina; Ekaterina Yu. Fedotova; Sergey N. Illarioshkin (Анналы клинической и экспериментальной неврологии)
Alzheimer disease (AD) is a chronic neurodegenerative disorder and the most common cause of dementia in the elderly. Current international guidelines for the clinical diagnosis of AD consider the diagnosis to be both clinical and biological. It requires a specific clinical phenotype and a confirmed biological origin based on biomarkers of amyloid and tau pathology. In Russia, only a few research centers perform laboratory diagnosis of AD using cerebrospinal fluid (CSF) biomarkers. Better access to laboratory diagnosis of AD and wider use of CSF biomarkers in clinical practice will help to assess the true prevalence of AD in the Russian population and to select patients for targeted pathogenic therapies based on the use of monoclonal antibodies against abnormal brain proteins, which have been actively developed in recent years. This review summarizes information on the main CSF biomarkers of AD and their diagnostic and prognostic value.